A severe case of iatrogenic lactation ketoacidosis. (9th March 2012) - Szulewski, Adam; Howes, Daniel; Morton, A Ross
Abstract : Lactation ketosis is a recognised disorder in postpartum lactating cows where a negative energy balance develops because the energy demands of milk production exceed the energy capacity of the animal. Rarely, nursing women can develop problems with lactation ketosis when their glycogen stores are depleted, causing the body to turn to gluconeogenesis as an energy substrate for galactopoiesis. The authors describe the case of a breastfeeding woman admitted to hospital and made nil per os (NPO) to treat a bowel obstruction. She did not receive intravenous glucose and 3 days postadmission developed a dangerous starvation ketosis (venous pH of 6.64). She was treated with intravenous dextrose, bicarbonate as well as cessation of breastfeeding and recovered quickly. Only four previous reports describe human lactation ketosis and this is the first iatrogenic case reported to our knowledge. It highlights the importance of addressing the unique caloric requirements of nursing women, especially when they are kept NPO.